Factors Contributing to the Married Men’s Attitudes Towards Wife-beating in Indonesia - Dyah Hapsari Ekonugraheni; Eva Lydia; Yusnaini Yusnaini; Mery Yanti (Journal of Social Behavior and Community Health)
Background: Domestic violence is a common problem in Indonesia, especially intimate partner violence (IPV). This study aims to analyze the predictors of attitudes of married men towards wife-beating (WB) for neglecting their children. Methods: The research data comes from the 7th Demography and Health Survey collected by the U.S. Agency for International Development in 2017. The respondents were 10,009 married male respondents aged 15-54 and responded to question 618 (Do you agree WB by husband for neglecting their children?). Results: The results showed that of the ten independent variables identified as predictors of married men’s attitude towards WB for neglecting their children, only six independent variables had a significant relationship, including adultery, age, smoking habit, location of residence, education level, and polygamy. Of these six independent variables, two independent variables (level of education and age) had a negative relationship, and four variables had a positive relationship with dependent variable significantly, p <0.01, with respective contributions of 82% (adultery), 121% (smoking habit), 125% (location of residence), and 233% (polygamy). The final logistic regression model can explain dependent variable of 2.06% significantly, X2 (6) = 170.43, p <0.01. Conclusion: This study suggests government institutions to make policy change in several sectors, such as education, social, information, tourism, health, economic, and regional development policy.